(untitled) (International journal of artificial intelligence, 2026)
This article scientifically analyzes the role and importance of artificial intelligence technologies in the online translation process. In particular, the technologies of neural machine translation (Neural Machine Translation – NMT), natural language processing (NLP) used in Russian-Uzbek translation systems, their advantages and linguistic problems are considered. According to the results of the study, although artificial intelligence-based translation systems have significantly increased the speed and scope of translation, the role of a human translator remains in terms of semantic accuracy, cultural context and stylistic compatibility.